ANALISIS RISIKO KECELAKAAN KERJA DENGAN METODE JOB SAFETY ANALYSIS PADA PROYEK PEMBANGUNAN HOTEL LASKA CIATER RESORT - Sabrina, Risye Nur; Rahayu, Sri (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2026)
Occupational Health and Safety (OHS) is an important thing in the world of work because workers are guaranteed occupational safety and health both physically and psychologically. However, the implementation of OHS in several companies, especially in construction projects, is still lacking in attention, which can lead to the risk of work accidents. Work accidents in a construction project can be minimized if you know and understand the risk of accidents in the work environment. This study aims to analyze the risk of work accidents in the Laska Ciater Resort Hotel construction project. The data analysis technique uses a descriptive qualitative method using the Job Safety Analysis (JSA) method to identify hazards and risks of work accidents. The results of the study showed that there were four occupational risk assessments, namely low risk, medium risk, high risk, and very high risk. The low risk level was found in 10 jobs with a total of 26 potential hazards. The medium risk level was found in 10 jobs with a total of 31 potential hazards. The high risk level was found in 6 jobs with a total of 6 potential hazards and the very high risk level was found in 1 jobs with a total of 1 potential hazards. Risk control can be categorized into 3 aspects, namely the worker aspect, the work environment aspect, and the work tool aspect.